Developing a Mobile Reduced Gravity Simulator - Mourlam, Timothy John (Kansas State University, 2012)
This thesis describes the design, development, and initial testing of the Mobile Reduced Gravity Simulator (MoRGS). MoRGS is a hoist with active force control, to be used in terrestrial environments with human test subjects for the simulation of partial gravity or zero gravity environments. It is to be used with the subject performing activities while being harnessed to the hoist. The following work here describes the mechanical design, structural and dynamic analyses, simulations used to aid in the control design and component selection, the development of unique control algorithms tailored to the objectives and uncommon dynamics of MoRGS, and initial testing performed without the use of human subjects. Major components of the MoRGS system include: AC servo motor, gearbox, custom-designed drum, pneumatic muscle, load cell, and a microprocessor. The system is designed to track the motion of the test subject over several meters of vertical travel at speeds of up to 2 Gs of acceleration. This allows for high performance during subject’s physical tests, including running on a treadmill and a climbing ladder. It is capable of offloading 50 lb. to 600 lb. and the level of desired reduced gravity is programmable. Results from testing of the system demonstrate that MoRGS system achieves its goals. It performs well, and the sensitivity of the force controller enables it to compensate for the most minute human motion disturbance.
Keywords: Controls NASA Simulator Robotics; NASA; Simulator; Robotics; Kinesiology (0575); Mechanical Engineering (0548); Robotics (0771)